Effect of applied potential on stress corrosion cracking behavior of X80 steel in alkaline soil simulated solution with sulfate-reducing bacteria. (March 2021) - Wang, Zeqi; Xie, Fei; Wang, Dan; Liu, Jiaqi
Highlights: Stress corrosion cracking of X80 steel under SRB, external potential and stress. The corrosion mechanism under the action of SRB and external potential was clarified. The stress corrosion sensitivity of X80 steel under different external potentials. Abstract: In this study, the effect of applied potential on stress corrosion behavior of X80 pipeline steel in Dagang soil containing sulfate-reducing bacteria was comprehensively analyzed by means of the AC impedance technique and slow strain-rate tensile tests and scanning electron microscope observation of fracture morphology. The results indicate that, with decreasing electrode potential, the corrosion degree of the sample first decreases and then increases, and the stress corrosion cracking sensitivity exhibits a certain rule. Under the Ecorr and a potential of −725 mV(vs.CSE), the stress corrosion cracking mechanism of metal is anodic dissolution. The synergistic effect of sulfate-reducing bacteria and stress results in the initiation and propagation of cracks on the surface of the metal electrode. At −1275 mV(vs.CSE), the mechanism of stress corrosion cracking is hydrogen-induced cracking. The sulfate-reducing bacteria exacerbates the cathodic hydrogen evolution at this potential. Under the combined effects of hydrogen and stress, stress corrosion cracking behavior occurs in metals.